Proportion of Coronary Angiography Results in Female Patients with Positive Treadmill Test Results - Suci Alma Harselia (ARKAVI [Arsip Kardiovaskular Indonesia), 2018)
Coronary heart disease is a general term for atherosclerosis or plaque occurs in the heart arteries that can cause a heart attack. Data from the American Heart Association (AHA), more than a third of adult women suffer from one form of cardiovascular disease. The heart training test uses a treadmill test or exercise test is the most common used modality and is the first diagnostic test recommended for detecting coronary heart disease. Women with positive results ischemic response are recommended to perform coronary angiography to determine the accuracy of the disease. The aims of reseach is the proportion of coronary angiography results in female patients with positive Treadmill Test results. Method of this study research uses descriptive research whose data is taken Cross Sectional at the Tangerang District General Hospital. The results obtained 24 patients, the percentage of female patients with Positive Treadmill Test results who performed cardiac catheterization with normal coronary angiography as many as 12 patients (50%), 6 non-significant coronary angiography results (25%), whereas the results of coronary angiography were not normal as many as 6 patients (25%). Based on age, female patients with Positive Treadmill Test and normal coronary angiography results were found to be the most at the age of 44-54 years. The conclusion was that female patients with Positive Treadmill Test results were mostly normal coronary angiography and were found at ages 44-54 years Keywords: Coronary Heart Disease in Women, Treadmill Test, Coronary Angiography Penyakit jantung koroner adalah istilah umum terjadinya aterosklerosis atau terjadi plak di arteri jantung yang dapat menyebabkan serangan jantung. Data dari American Heart Association (AHA), lebih dari sepertiga perempuan dewasa menderita salah satu bentuk Penyakit Kardiovaskular. Uji latih jantung menggunakan tes treadmill dan merupakan modalitas yang paling sering digunakan dan merupakan tes diagnostik pertama yang direkomendasikan untuk mendeteksi Penyakit Jantung Koroner. Perempuan dengan hasil Treadmill Test Positif dianjurkan melakukan angiografi koroner untuk menentukan keakuratan penyakit. Penelitian ini bertujuan untuk mengetahui proporsi hasil angiografi koroner pada pasien perempuan dengan hasil Treadmill Test positif. Penelitian ini menggunakan metode penelitian deskripstif yang datanya diambil secara Cross Sectional di Rumah Sakit Umum Kabupaten Tangerang. Hasil penelitian didapatkan 24 pasien, persentase pasien perempuan dengan hasil Treadmill Test Positif yang menjalankan tindakan kateterisasi jantung dengan hasil angiografi koroner normal sebanyak 12 pasien (50%), hasil angiografi koroner non signifikan sebanyak 6 pasien (25%), sedangkan hasil angiografi koroner yang tidak normal sebanyak 6 pasien (25%). Berdasarkan usia, pasien perempuan dengan Treadmill Test Positif dan hasil angiografi koroner normal ditemukan paling banyak pada usia 44-54 tahun. Kesimpulan penelitian ini yaitu pasien perempuan dengan hasil Treadmill Test Positif kebanyakan hasil angiografi koronernya normal dan banyak ditemukan pada usia 44-54 tahun. Kata Kunci: Penyakit Jantung Koroner pada Perempuan, Treadmill Test, Angiografi Koroner